Heterogeneity of asthma according to blood inflammatory patterns. Issue 5 (8th January 2009) - Nadif, R; Siroux, V; Oryszczyn, M-P; Ravault, C; Pison, C; Pin, I; Kauffmann, F
Abstract : Rationale: There is increasing interest regarding asthma heterogeneity in relation to inflammatory patterns. Objectives: To assess phenotypic characteristics, in particular clinical presentation of the disease, in 381 well-characterised adults with asthma from the French Epidemiological study on the Genetics and Environment of Asthma (EGEA) according to their blood inflammatory pattern. Methods: Four blood inflammatory patterns were defined according to eosinophil (EOS) and neutrophil (NEU) count cut-off points. Samples with ⩾250 EOS/mm 3 were classified as EOS hi and those with ⩾5000 NEU/mm 3 as NEU hi . Clinical characteristics include typical asthma and chronic obstructive pulmonary disease (COPD)-like symptoms, as well as composite quantitative scores addressing the activity of the disease. Results: A substantial number of those with asthma (56.2%) had the EOS lo pattern (<250 EOS/mm 3 ). Patients with asthma who had the EOS hi pattern had higher immunoglobulin E (IgE), a lower forced expiratory volume in 1 s (FEV1 ) and presented a more active asthma than those with the EOS lo pattern. Among those with the EOS lo pattern, neutrophil inflammation (NEU hi ) was related to a less frequent positive skin prick test response (OR 0.44, 95% CI 0.20 to 0.96). Among those with the EOS hi pattern, neutrophil inflammation did not explain current asthma or asthma activity, and was significantly related to nocturnal symptoms (OR 5.21, 95% CI 1.44 to 18.8) independently of age, sex, smoking and inhaled corticosteroid treatment. In non-smokers with asthma, COPD-like symptoms, in particular chronic phlegm, were more frequent in those with neutrophil inflammation, independent of eosinophil inflammation (OR 2.35, 95% CI 1.08 to 5.10). Conclusions: Besides eosinophilia, neutrophil inflammation assessed in the blood is related to specific characteristics of asthma. Considering simultaneously neutrophilic and eosinophilic inflammation may contribute to help to disentangle this complex disease.